Impacts of metal contamination and eutrophication on dinoflagellate cyst assemblages along the Guangdong coast of southern China. Issue 1 (15th July 2017) - Lu, Xinxin; Wang, Zhaohui; Guo, Xin; Gu, Yangguang; Liang, Weibiao; Liu, Lei
Abstract: Fifty-one surface sediment samples were collected from eleven sea areas along the Guangdong coast in southern China. Biogenic elements, metals and dinoflagellate cysts were analyzed. Twenty-one cyst taxa in 12 genera were identified. The cyst concentrations ranged between 14 and 250 cysts/g, with an average of 69 cysts/g. The low cyst production was caused by coarse sediments, high sedimentation rates, and high anthropogenic disturbances. Biogenic elements were comparable with those reported. However, the metal concentrations were far lower than the sediment quality guidelines. Both biogenic elements and metals were higher in the Mid Coast and lower in the Western Coast. Eutrophication slightly enhanced the productivity of autotrophic dinocysts, and cysts of Scrippsiella indicated eutrophication. Cd had inhibitory effects on cyst production. Alexandrium and Diplopsalis cysts were sensitive to metal contamination; however, Gyrodinium, Pheopolykrikos, and Lingulodinium cysts had high resistance to metal contamination. Graphical abstract: Highlights: Fifty-one surface sediment samples were collected from Guangdong coast of China. Biogenic elements, metals and dinoflagellate cysts were analyzed. Cyst concentrations were low and cysts of Protoperidinium dominated. Cd had inhibitory effects on cyst production. High eutrophication in the Mid Coast slightly increased cyst productivity.